Factors Associated with the Response Time of Health Workers in the Emergency Room at Langsa Regional General Hospital - Junaidi; Muhammad Husaini; Linda Jurwita; Novita Sari (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Response time in the emergency department plays a crucial role in determining patient outcomes. Factors such as age, gender, experience, and emergency training may influence the speed of healthcare workers' responses. This study used a cross-sectional quantitative design involving 36 healthcare workers in the emergency department. Data were collected through a structured questionnaire covering demographics, experience, and participation in emergency training, and analyzed using the chi-square test (p<0.05). Results showed that most respondents demonstrated fast response times. Significant associations were found between response time and age (p=0.041), emergency experience (p=0.003), and training participation (p=0.029), but not with gender (p=0.273). These findings highlight the importance of hands-on experience and regular training in enhancing healthcare workers' preparedness and responsiveness in critical situations.